False aneurysm of the common femoral vein in a footballer - (:unkn) unknown (B M J PUBLISHING GROUP, 2005)
Traumatic false aneurysm of the femoral vein has never been reported in the English literature. The case is here reported of a footballer with a traumatic false aneurysm of the common femoral vein which was initially misdiagnosed as an arterial pseudoaneurysm. This is a very rare clinical condition, but this diagnosis should be among those considered for post-traumatic unexplained thigh pain after trauma.
Keywords: TRAUMATIC VENOUS ANEURYSM